(untitled) (Third Sector Social Economic Review, 2017)
European countries, the United States and other developed countries have supported cooperatives and have created an environment where many individuals producing products / services could move together. The main purpose of cooperatives is to meet the needs of its members (owners) and not to make profit. The remaining revenues after deducting costs are distributed to the shareholders in cooperatives. Nowadays, agricultural cooperatives are one of the most effective tools especially in the development of the countries having agriculture-based economy. Cooperative managers and their partners need to be trained about cooperative system for agricultural cooperatives to be successful. In addition, strategic plans must be formed by analyzing the current state of cooperatives. The purpose of this study is to determine the current state of agricultural development cooperatives operating in Usak and determine their advantages and disadvantages. In this study, the strengths and weaknesses, opportunities and threats of agricultural development cooperatives operating in Uşak were tried to be determined by using the SWOT analysis.